Comparison of the effect of adding different levels of digestarom and probiotics in the diet on some productive and measurements of intesti-nal lengths and weights system of boiler chickens - Fairooz, Liza Ali; Kadhim, Mohammed Jard (Journal of Kerbala for Agricultural Sciences, 2023)
This study aimed to assess intestinal length in broiler chickens and ascertain the impact of plant extracts, represented by Digestarome, on various anatomical parameters for the digestive system, in comparison to microorganisms. The research used 450 one-day-old broiler chicks, which were reared for five weeks. The results showed a significant improvement (P < 0.05) in feed consumption each week (5-1) for both treatments (T5 and T6) during the course of the trial when compared to the control treatment (T1). Overall treatments, there was a significant improvement in the feed conversion factor at the P < 0.05 level. Furthermore, the mixture treatment's average live body weight varied every week until it reached the fifth treatment (T5). The rates of live body weight in the two treatments (T2 and T3) significantly declined in the week (2-4), whereas the rates of weight gain in all weeks significantly increased in the treatments (T5 and T6) Additionally, a notable improvement was noted in support of the therapy. (T4, T5, and T6), as they recorded a significant superiority in the rate of weight gain for all weeks. Clearing with significant differences between the treatments about carcass cuts for the treatments (T5 and T6) the highest value was recorded. As for the weight and length of the intestines, all of the additional treatments outperformed the control treatment (T1) about the weight of the intestines. As for the intestine length, the sixth treatment (T6) outperformed significantly. (P<0.05) on the control treatment (T1) and did not differ significantly from the other addition treatments.